Severe Combined Kidney Injury in an Hiv-Infected Patient Receiving Antiretroviral Therapy (Clinical Observation) - O. N. Vetchinnikova; V. P. Suslov; Ya. A. Afanas'eva; A. M. Fomin (SINAPS LLC, 2024)
Kidney injury in patients infected with the human immunodeficiency virus (HIV) has a diverse spectrum. Some antiretroviral therapy (ART) drugs have nephrotoxic effects. We present a clinical case of severe combined kidney injury - chronic kidney disease (CKD) and acute kidney disease (AKD) - in a patient with HIV infection. She was on long-term treatment with a fixed-dose combination of rilpivirine, tenofovir, and emtricitabine and had normal pre-treatment renal function (estimated glomerular filtration rate 69 mL/min/1.73m2 ). There was gradual increase in blood creatinine, but the patient did not visit a nephrologist and the ART was not changed. The patient was admitted to the nephrology department two years later because she had arterial hypertension and hyperazotemia (blood creatinine 718 μmol/l). Diagnosis: chronic tubulointerstitial nephritis, CKD G5 taking into account the gradual increase in blood creatinine during long-term ART. The patient was treated with peritoneal dialysis. There was persistent decrease and stabilization of blood creatinine (210-190 μmol/l was) which indicated in AKD. The presented observation demonstrates that ART in an HIVinfected patient can lead to the development of severe combined chronic and acute kidney injury. HIV-infected patients receiving ART require regular monitoring of renal function and follow-up by a nephrologist.